MEMBANGUN RUMAH TINGGAL SYARIAH: Sebuah Pendekatan Fikih Arsitektur - Jefry Tarantang (Al-Maslahah : Jurnal Ilmu Syariah, 2022)
This paper discusses the construction of residential houses that are in accordance with sharia principles, both in the art and science of designing and making construction of buildings and residences, which are then called architectural fiqh. Apart from paying attention to architecture, housing construction must also pay attention to aspects of Islamic law. All this time, the study of architecture has focused more on Islamic architecture, but no one has studied architecture in the fiqh approach. So that through the fiqh approach a new study was initiated, namely fiqh architecture. The method used in this study is an empirical-normative method that analyzes qualitatively and prescriptive using the fiqh approach, conceptual approach and contextual approach to spatial architecture. The findings of this study indicate that the construction of houses so far only pay attention to aspects of architecture only, so the need for a fiqh and architecture approach (fiqh architecture), namely building houses in accordance with sharia signs such as aspects of worship, muamalah, neighboring manners and 'urf applicable in society. Through the approach of fiqh architecture, directing to build and maintain sharia dwellings that are in accordance with sharia maqashid, namely maintaining religion, soul, reason, descent, and property.